2018
DOI: 10.1155/2018/3103986
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Next-Generation Sequencing of a Deafness Gene Panel (MiamiOtoGenes) Analysis in Families Unsuitable for Linkage Analysis

Abstract: Hearing loss (HL) is a common sensory disorder in humans with high genetic heterogeneity. To date, over 145 loci have been identified to cause nonsyndromic deafness. Furthermore, there are countless families unsuitable for the conventional linkage analysis. In the present study, we used a custom capture panel (MiamiOtoGenes) to target sequence 180 deafness-associated genes in 5 GJB2 negative deaf probands with autosomal recessive nonsyndromic HL from Iran. In these 5 families, we detected one reported and six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Custom capture or targeted gene sequencing has been a cost‐effective approach to detect mutations in genes known to be associated with a specific disease condition (Aparisi et al, ; Bonachea et al, ; Patel et al, ; Rehm, ; Shang et al, ; Trujillano et al, ; X. Wang et al, ). Previous studies exploring mutations in coloboma‐associated genes have been limited to a subset of genes in affected families (Gonzalez‐Rodriguez et al, ; Williamson & FitzPatrick, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Custom capture or targeted gene sequencing has been a cost‐effective approach to detect mutations in genes known to be associated with a specific disease condition (Aparisi et al, ; Bonachea et al, ; Patel et al, ; Rehm, ; Shang et al, ; Trujillano et al, ; X. Wang et al, ). Previous studies exploring mutations in coloboma‐associated genes have been limited to a subset of genes in affected families (Gonzalez‐Rodriguez et al, ; Williamson & FitzPatrick, ).…”
Section: Discussionmentioning
confidence: 99%
“…Custom capture or targeted gene sequencing has been a cost-effective approach to detect mutations in genes known to be associated with a specific disease condition (Aparisi et al, 2014;Bonachea et al, 2014;Patel et al, 2018;Rehm, 2013;Shang et al, 2018;Trujillano et al, 2014; X. Wang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A previously reported stopgain variant (c.4936C>T; p.R1646X) (Wesdrop, 2017) in LOXHD1 (NM_144612.6; NP_653213.6) was identified in family KF-18. A previously reported splice variant (Schrauwen et al, 2012) c.637 + 1G>T in CABP2 (NM_016366.3; (Shang et al, 2018). A novel missense variant c.1190C>T (p.A397V), predicted to be pathogenic, was identified in MYO7A in KF-2.…”
Section: Resultsmentioning
confidence: 85%
“…Patients homozygous for R1746Q have been reported show symptoms of ''atypical Usher syndrome'' with variable retinal phenotypes (Bolz et al, 2001;Astuto et al, 2002). In the Iranian population, 13 missense and 2 splice CDH23 mutations have been identified (Sloan-Heggen et al, 2015;Bademci et al, 2016;Ghasemnejad et al, 2017;Shang et al, 2018). The stopgain variant USH1C c.628A>T (p.K210X) in KF-4 has been previously observed only in a Turkish family (Bademci et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…To date, over 30 point mutations have been reported in the TRIOBP gene. Previous studies have suggested exon 7 of TRIOBP as a hotspot for mutations, probably due to presence of repetitive sequences 32,34 . The protein contains two types of domains, N‐terminal pleckstrin homology (PH) and C‐terminal coiled‐coil.…”
Section: Discussionmentioning
confidence: 99%